DIRECTIONS FOR USING DIGITAL TECHNOLOGIES IN DEVELOPING THE EXPORT COMPETENCE OF ENTERPRISES (Marketing Journal, 2025)
This article presents a theoretical analysis of the key factors influencing export potential through digital technologies. The study is based on international scholarly sources and covers all stages from production to marketing and logistics. A conceptual model illustrates how digital transformation promotes multi -level integration in export activities. The research serves as a foundation for practical recommendations developed through a theoretical approach.
Keywords: digital technologies; export potential; digital transformation; conceptual model; international trade; strategic development